Uncoupling of the Electron Transport Chain Compromises Mitochondrial Oxidative Phosphorylation and Exacerbates Stroke Outcomes - Grasmick, Kimberly A (J Neuroinfect Dis, 2018)
OBJECTIVE: Mitochondrial dysfunction is known to be implicated in stroke, but the complex mechanisms of stroke have led to few stroke therapies. The present study to disrupted mitochondrial oxidative phosphorylation through a known electron transport chain (ETC) uncoupler, Carbonyl cyanide-4 (trifluoromethoxy) phenylhydrazone (FCCP). Analyzing the resulting neurological deficits as well as infarct volume could help determine the role of mitochondria in stroke outcome and determine whether uncoupling the ETC could potentially be a strategy for new stroke therapies. The objective of this study was to determine the effects of uncoupling electron flow on mitochondrial oxidative phosphorylation and stroke infarction. METHODS: Cerebral endovascular cells (CECs) were treated with various concentrations of FCCP, and bioenergetics were measured. For the stroke mouse model, FCCP (1 mg/kg, i.p) or vehicle was administered followed by 1-hour transient middle cerebral artery occlusion (tMCAO). Infarct volume was measured after a 23-hour reperfusion, and triphenyl tetrazolium chloride (TTC) staining was used to assess infarct volume. RESULTS: FCCP significantly decreased basal respiration, ATP turnover, maximal respiration, and spare capacity when the concentration of FCCP was greater than 1000 nM. The mice pretreated with FCCP had a significantly increased infarct volume within the cortex, striatum, and total hemisphere. Mice receiving FCCP had a significantly increased neurological deficit score compared to the vehicle. CONCLUSIONS: FCCP compromised mitochondrial oxidative phosphorylation in CECs in a dose-dependent manner. Uncoupling the electron transport chain with FCCP prior to tMCAO exacerbated stroke infarction in mice.